Cooperative Bimanual Action - Hinckley, Ken; Pausch, Randy; Proffitt, Dennis; Patten, James; Kassell, Neal (CHI '97 Proceedings of the ACM SIGCHI Conference on Human factors in computing systems, 1997)
We present an experiment on cooperative bimanual action. Right-handed subjects manipulated a pair of physical objects, a tool and a target object, so that the tool would touch a target on the object. For this task, there is a marked specialization of the hands. Performance is best when the left hand orients the target object and the right hand manipulates the tool, but is significantly reduced when these roles are reversed. This suggests that the right hand operates relative to the frame-of-reference of the left hand. Furthermore, when physical constraints guide the tool placement, this fundamentally changes the type of motor control required. The task is tremendously simplified for both hands, and reversing roles of the hands is no longer an important factor. Thus, specialization of the roles of the hands is significant only for skilled manipulation.